Analisis Morfometri DAS untuk Pemetaan Kerawanan Banjir Bandang di Kecamatan Runjung Agung, Kabupaten Ogan Komering Ulu Selatan - Egi Saputra; Budhi Setiawan; Dede Nurohim (Geosfera: Jurnal Penelitian Geografi, 2026)
South Ogan Komering Ulu Regency is characterized by complex topography and well-developed drainage networks that may increase flash flood susceptibility. Although morphometric analysis has been widely applied in hydrological studies, the integration of linear, relief, and areal morphometric parameters for flash flood susceptibility mapping in Runjung Agung District remains limited. This study aims to analyze watershed morphometric characteristics and map flash flood susceptibility in Runjung Agung District and its surrounding areas. The analysis was conducted using Digital Elevation Model (DEM) data within a Geographic Information System (GIS) environment through the calculation of 15 morphometric parameters representing linear, relief, and areal characteristics. All parameters were normalized into a 0–1 index and integrated using the Cell Statistics method to generate a flash flood susceptibility map. The results indicate that high-susceptibility zones are concentrated in the central, northeastern, southwestern, and southeastern parts of the study area, particularly around Tanjung Kurung, Runjung Agung, Saung Naga, Simpang Saga, Kota Karang, and Negeri Batin. These areas are characterized by dense drainage networks, short overland flow lengths, and relatively high relief conditions. The findings demonstrate that DEM-based morphometric analysis provides an effective approach for identifying flash flood-prone areas and supporting disaster mitigation planning.